Chapter 15. Root Crop Production: VPH ch. 15, CV300/HS965, rev. 6/2024 - Beuzelin, Julien; Dittmar, Peter J.; Wells, Bonnie; Desaeger, Johan; Zotarelli, Lincoln; Zhang, Shouan; Wang, Qingren; Frey, Craig; Meszaros, Anna (EDIS, 2024)
Chapter 15 of the Vegetable Production Handbook of Florida